Analisis Pembagian Tugas dan Job Description : Pada Agung Fotocopy Centre - Ida Bagus Suarditha; Edy Chandra (Widya Manajemen, 2026)
Task allocation and job description are essential elements of human resource management in ensuring role clarity and work effectiveness. However, in micro and small enterprises, task distribution is often implemented flexibly without formal documentation. This study aims to analyze task allocation and job description practices at Agung Fotocopy Centre, a micro-scale printing service business. This research employed a qualitative approach with a descriptive method. Data were collected through direct observation and in-depth interviews with the business owner and employees, and analyzed descriptively by comparing field findings with human resource management concepts. The results indicate that task allocation at Agung Fotocopy Centre is characterized by multitasking and the absence of written job descriptions. Although this flexible system supports operational continuity, it also creates potential role ambiguity and task overlap. This study concludes that micro enterprises require simple and adaptive job descriptions to maintain work flexibility while enhancing role clarity and effectiveness.